The Role of Public Legal Awareness in Efforts To Prevent Illegal Gold Mining - Jhoni Lie; Ade Adhari (UNISSULA Semarang, 2026)
Illegal Gold Mining (PETI) is a persistent problem in various regions in Indonesia. This activity not only causes state losses in terms of tax revenue and levies, but also impacts environmental damage and threatens public safety. One factor contributing to the continued prevalence of illegal gold mining is the low level of public legal awareness regarding the importance of complying with mining licensing provisions. This study aims to analyze the role of public legal awareness in preventing illegal gold mining practices and identify obstacles faced in increasing such legal awareness. This study uses an empirical legal research method with a socio-legal approach. The results indicate that public legal awareness plays a significant role in preventing illegal gold mining practices through increasing understanding of legal regulations, compliance with licensing provisions, and community participation in protecting the environment. However, economic factors, low levels of education, and suboptimal legal socialization remain major obstacles. Therefore, synergy is needed between the government, law enforcement officials, and the community to increase legal awareness in order to realize sustainable mineral resource management.